A Rotation-Based Method for Bolt and Belleville Spring Preloading for Seismic Friction Sliding Structural Connections - Ramhormozian, Shahab; Clifton, G Charles; Davet, George P (Elsevier BV, 2025)
Seismic friction sliding structural connections have been a focus of research and development for over four decades, due to their potential to act as energy-dissipating fuses, dissipating energy through friction and limiting forces. One of the key challenges in the design and implementation of these connections is achieving accurate and precise clamping force through bolt tightening. An overestimated clamping force can lead to premature sliding, while an underestimated force can delay the onset of sliding and cause excessive damage during a severe earthquake. Achieving a precise clamping force during installation and maintaining it throughout the structure's lifetime is very important. Well-designed Belleville Springs (BeSs) have been identified as a significant component in enhancing the seismic behaviour of these connections, by ensuring stable sliding behaviour and maintaining clamping force under both static and dynamic conditions. Despite their effectiveness, there is a lack of standardized methods for tightening bolts with BeSs to reliably achieve a desirable level of bolt tension within the elastic range. This paper presents findings from 69 bolt tightening experiments conducted on various configurations and BeS types and arrangements. Key parameters such as imposed torque on the nut, BeS deflection, and nut rotation were measured and analyzed. A nut rotation-based method is proposed to ensure that the desired level of bolt tension is consistently achieved, offering a practical solution for both on-site and workshop applications in seismic friction-sliding connections.
Keywords: 0905 Civil Engineering; 0915 Interdisciplinary Engineering; 1202 Building; Civil Engineering; 4005 Civil engineering